2022
DOI: 10.2147/opth.s369673
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the American Glaucoma Society Membership on Current Glaucoma Drainage Device Placement and Postoperative Corticosteroid Use

Abstract: Purpose To assess practice patterns and opinions of glaucoma specialists regarding glaucoma drainage device tube shunt placement and post-operative anti-inflammatory medication use. We also assess the perceived need for a randomized control trial to compare them. Patients and Methods An online survey was distributed to a group of glaucoma specialists from the American Glaucoma Society via the American Glaucoma Society forum from April to August 2021. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a 2022 AGS survey, 90% of the surveyed glaucoma surgeons reported commonly utilizing the AC for tube placement, but 61% reported that the available evidence suggests the superiority of sulcus placement over the AC in terms of ECL. Interestingly, 77% of surgeons reported that they would convert to placing tubes in the sulcus if a randomized controlled trial were to show its superiority in preventing ECL [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2022 AGS survey, 90% of the surveyed glaucoma surgeons reported commonly utilizing the AC for tube placement, but 61% reported that the available evidence suggests the superiority of sulcus placement over the AC in terms of ECL. Interestingly, 77% of surgeons reported that they would convert to placing tubes in the sulcus if a randomized controlled trial were to show its superiority in preventing ECL [ 15 ].…”
Section: Discussionmentioning
confidence: 99%